Identification of Lactic Acid Bacteria in Tapioca Waste Based Local Microorganism Starter with Different Molasses Addition: Identifikasi Bakteri Asam Laktat dari Starter Mikroorganisme Lokal Asal Onggok dengan Penambahan Molases yang Berbeda - Fitria, Restuti; Hindratiningrum, Novita; Falah, Muhammad (BPFP Universitas Bengkulu, 2025)
The fermentation process requires a starter as a source of microorganisms. One of the microorganisms involved in the fermentation process is Lactic Acid Bacteria (LAB). Utilizing organic waste such as tapioca waste as a source of local microorganisms (MOL) for feed fermentation starter can not only improve feed quality, but also reduce the negative impact of poorly managed industrial waste on the environment. In addition, the utilization of molasses as a carbohydrate source in the preparation of starters can be done because it doesn’t compete with food. The aim of the study was identify LAB starter of tapioca waste with the addition of molasses at different levels. This research was conducted using descriptive qualitative and quantitative methods. There were 3 treatments, namely tapioca waste MOL starter with molasses addition of 20%(A), 30%(B), and 40%(C) respectively. The research variables observed were pH, morphological characteristics and total of LAB. The results showed that the pH produces ranged from2,45 to 2,63 and the average size of bacteria derived from all treatments was punctiform with white color, circular configuration, flat elevation, and entire margin. Based on gram straining, it was found that the bacteria growing in all treatments were gram-positive, non-spore-forming, and rod-shaped bacteria. The highest total LAB was obtained in treatment A, which was 50,4x105 CFU/ml. The conclusion is that based on the pH produces, the quality of MOL starter from each treatment is very good and the presence of LAB in all treatments with morphological characteristics of cells that are almost the same and show morphological characteristics of Lactobacillus.